Feeding habitat of the understory arboreal snail Tikoconus costarricanus (Stylommatophora: Euconulidae) in a tropical montane wet forest, Costa Rica (UNED Research Journal, 2021)
Introduction: The feeding habitats of land snails are essential for their survival. Some are little known, for example the upper surface of leaves, habitat of tropical arboreal and shrub snails. Objective: To analyze the feeding behavior and preferences in the feeding habitat of the tropical snail Tikoconus costarricanus. Methods: In a humid montane tropical forest in Cartago, Costa Rica, I recorded every 3 to 4 hours the feeding activity and general behavior of individually marked snails on a 2km trail (seven 24-hour visits in May 2010-March 2011). Results: I observed a total of 167 individual specimens and made 781 observations about their behavior and the leaves on which they were found. These snails preferred monocotyledonous leaves with many epiphylls, despite the fact that those leaves were not common in this forest. They avoided ferns, and during the less rainy season, they preferred leaves with many trichomes, although there were few such leaves. On average, they spent 11 hours on each individual leaf and visited two leaves per day. The few snails seen on stems were almost always moving, as opposed to those on the leaf underside. On average they moved a net 65 cm each day. Feeding concentrated around 9:00 am and defecation around 4:20 am. Conclusions: These snails prefer leaves with many epiphylls, where they find good camouflage, moisture and food. The preference for trichomes could be due to mechanical reasons. The lack of seasonality in their behavior may reflect their stable food source in a forest that remains humid year round.
Keywords: Seasonality; Microhabitat; Epiphylls; Land snails; Feeding